2008
DOI: 10.1007/s00381-007-0556-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular schwannoma in a 15-year-old adolescent: a case report

Abstract: This case report illustrates a right occipital horn schwannoma in a 15-year-old adolescent boy who was successfully treated with surgical resection and discusses the possible origins of the tumor in this unique location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…It has also been suggested that intra-axial schwannomas could arise from neural crest cells displaced into the nervous system as a result of failed migration in embryonic life 1 . This disordered embryogenesis theory may account for the relationship between intraventricular schwannomas and other neurocutaneous syndromes such as neurofibromatosis, Hirschprung's disease, and Waardenburg's syndrome 3,6 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has also been suggested that intra-axial schwannomas could arise from neural crest cells displaced into the nervous system as a result of failed migration in embryonic life 1 . This disordered embryogenesis theory may account for the relationship between intraventricular schwannomas and other neurocutaneous syndromes such as neurofibromatosis, Hirschprung's disease, and Waardenburg's syndrome 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the occurrence of a nerve sheath tumour in central nervous tissue is unexpected 1.2 . There are eleven case reports of ventricular schwannomas 3,[7][8][9] . The majority of these were located in either the lateral or fourth ventricles [4][5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations